Total quality management in the Singapore hotel industry - Ng, Sharon Ling Wan (2008)
The purposes of this study were two-fold: first, to determine whether hotels in Singapore practice Total Quality Management and secondly, to establish the necessity and suitability of the ISO 9002 certification as guidelines for TQM in the hospitality industry. Face-to-face interviews with 17 respondents from 14 leading hotels in Singapore were conducted to obtain a set of comprehensive information for the research.